Perlindungan Hukum Terhadap Anak Perempuan Korban Kekerasan Seksual di PPA Polresta Banjarmasin - Syaufi, Ahmad (IAIN Pekalongan, 2017)
Violence against girls lately increasingly widespread, whether physical, psychological, and sexual.  To provide services and protection against the girl child victims of crime, especially the crime of sexual violence, the police have established Women and Children Unit (Unit PPA).  This study aims to identify and analyze the obstacles faced  Unit PPA Polresta Banjarmasin in providing legal protection for women victims of child sexual abuse. This research uses empirical legal research with the research conducted analytical descriptive and explanatory. The types of data used in this study included primary data in the form of interviews and the question as written, and secondary data.The results showed that the obstacles faced Unit PPA Polresta Banjarmasin in providing legal protection, among others: victims hesitate to report, the family and the community who do not understand and tend to blame victims for sexual violence, the revocation of a report from the victim, the suspect fled, sexual violence is usually carried out at night in bed days, and the lack of facilities and infrastructure owned Unit  PPA Polresta Banjarmasin.